A case report of open-aorta, direct transcatheter valve-in-valve implantation: an innovative approach to manage the hazard of coronary flow compromise in transcatheter aortic valve re-interventions. Issue 5 (17th May 2021) - Calcaterra, Domenico; Kaur, Navneet; Dasari, Gopika; Daniel, George
Abstract: Background: Coronary flow compromise is a significant risk of transcatheter aortic valve therapy. Warranting preservation of coronary flow is even more challenging with transcatheter aortic valve re-intervention since the implantation of a transcatheter valve within a degenerated bioprosthetic or transcatheter valve increases significantly this hazard. Case summary: We present a case of heart failure secondary to transcatheter aortic valve degeneration requiring a transcatheter aortic valve re-intervention. Pre-operative imaging studies demonstrated a high risk for iatrogenic coronary flow impairment. The patient underwent a successful surgical removal of the prosthetic valve leaflets followed by direct transcatheter aortic valve implantation. Conclusion: We reviewed the literature on the approach to difficult coronaries in transcatheter aortic valve therapy, and we describe an innovative hybrid approach that may represent a viable alternative in cases where catheter techniques of coronary flow preservation are not applicable.